ANALISIS PERMINTAAN DAN PENAWARAN BERAS DI PROVINSI SUMATERA UTARA - Wahidin Tarigan; Zulkarnaian Lubis; Zahari Zein (Universitas Medan Area, 2018)
This study analyzes the demand and supply of rice , as well as looking at the effect of price and non- price variables on demand, supply of rice in the province of North Sumatra . The results showed that rice production is strongly influenced by the price of rice and fertilizer prices , the rise in the price of rice will memngkatkan number of offers in the future , whereas the increase in the price of fertilizer will reduce the number of betas offer , as a component of fertilizer inputs which are relatively large , while the price of substitute goods does not affect the rice offers . Views and expectations and the price elasticity of both input prices and terms of the demand is inelastic , the price of rice and the price variable substitutes insignificant influence on the demand for rice , the rise and fall of both vaniabel will not cause a change in the number of requests , while income and population positive effect on demand rice , when viewed in rice prices and good elasticity and income are both inelastic. Keyword : demand, supply, and rice